Mengawal Anggota Legislatif Mewujudkan Pemerintahan yang Bersih* - M Muslih (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
Legislative members are partners as well as balancing the government in regulating and controlling the government, therefore it is necessary to have a "presence" of honest and clean professional legislators. Reality shows that the professionalism of some legislators still disappoints some of their constituents. For this reason, it is necessary to think about how to escort members of the legislative body in order to realize a clean government. To meet these expectations an election process is needed that can guarantee the implementation of an honest and fair election process. In order to realize the ideal above, the presence of a good legislative Election Law, a professional law enforcement apparatus, and a culture of high legal awareness from the public in exercising their voting rights.